Consumer Personality Traits, Service Expectations, and Loyalty: Evidence from Local Beauty Salon in Jaffna in Sri Lanka - Senevirathne, P.V.D.; Hansika, W.A.K.A.; Ranasinghe, K.R.P.M.; Karunathilake, R.L.A.M.; Thadikara, T.M.S.T.; Bandara, H.M.S.M.; Vithanage, M.Y.D.; Madushanka, K.D.N.; Kushan, E.M.C.; Bandara, K.W.H.D.S.; Puvitharan, R.; Dilogini, S. (Faculty of Management Studies | Rajarata University of Sri Lanka, 2025)
Customer loyalty is very important for the survival and growth of micro, small, and medium enterprises (MSMEs) in the beauty and personal care industry. Despite its significance, little research has explored how personality traits influence service expectations in local beauty salons. To address this, the study aimed to explore the link between customer personality traits, service expectations, and loyalty in beauty salons in Jaffna, Sri Lanka. This study employed a qualitative approach, using a purposive sample that included three semi-structured interviews with a salon owner, a staff member, and a customer, along with five focus group discussions with 20 participants. This helped capture different viewpoints and showed how personality differences shape customer experiences, with thematic analysis highlighting these insights. The findings revealed that personality traits, especially openness to experience and conscientiousness, play a strong role in customer expectations and loyalty. Customers high in openness were more willing to try new hairstyles, treatments, and innovations. Conscientious customers valued cleanliness, punctuality, reliability, and consistent service quality. These expectations affected satisfaction, which in turn influenced loyalty behaviours such as returning to the same salon, recommending it to others, and resisting the urge to switch. The study also highlighted practical steps for salon owners, such as offering innovative services for open customers, ensuring reliability and hygiene for conscientious customers, and building close relationships with clients. Using social media to show both creativity and consistency was also useful for strengthening loyalty. Overall, this study links personality psychology to consumer behaviour in MSMEs, signifying the importance of cultural and community-specific factors. Furthermore, it provides new insights strengthened by linking the findings to broader service and consumer behaviour literature by integrating personality psychology with service expectations and loyalty in the beauty and personal care context.
Keywords: Beauty and personal care industry; Consumer behaviour; Loyalty; MSMEs; Personality traits; Service expectations